Determinants of Labor Participation and Wages toward People with Disabilities in Indonesia - Ririn Nopiah; Evita Hanie Pangaribowo (Indonesian Journal of Disability Studies, 2023)
Reductions in the supply of labor and wages occur to people with disabilities. Disability conditions cause a decline in productivity so that the probability of being a labor is small, risk of unemployment and loss of income. The high prevalence of disabilities in Indonesia causes inequality of labor participation and wages for disabilities in Indonesia based on the type of disabilities. The data used is Indonesia Family Life Survey (IFLS) waves 4 and 5 by pooled cross-section. The analysis methods are logit and tobit models. The results showed that communicative disabilities have a higher chance of labor participation and wages. Factors of the degree of severity, age, male, head of household, education, urban, chronic disease, ownership of insurance, and ownership of assets also affect labor participation and wages for disabilities. The labor activation program for disabilities is a succession and initiative as welfare reform, poverty alleviation and an indicator of inclusive development.